Fluid formulations: A study of varied interpretations of Madhesi identity (HIMALAYA, 2022)
This paper is an examination of the ways in which the residents and political actors of the Tarāi-Madhes (lowlands) in Nepal construct and contest Madhesi identity. It juxtaposes interpretations of Madhesi along geographic, linguistic, ethnic, and religious lines, with the experiential aspect of “being a Madhesi.” The paper demonstrates how Madhesi evolved into a politically charged, emotion-laden identity category, and argues that the experience of being othered is central to the construction and reification of Madhesi identity.